2021
DOI: 10.1016/j.reth.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Secreted matrix metalloproteinase-14 is a predictor for antifibrotic effect of IC-2-engineered mesenchymal stem cell sheets on liver fibrosis in mice

Abstract: Introduction Transplantation of IC-2-engineered bone marrow-derived mesenchymal stem cell (BM-MSC) sheets (IC-2 sheets) was previously reported to potentially reduce liver fibrosis. Methods This study prepared IC-2-engineered cell sheets from multiple lots of BM-MSCs and examined the therapeutic effects of these cell sheets on liver fibrosis induced by carbon tetrachloride in mice. The predictive factors for antifibrotic effect on liver fibrosis were tried to identify i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Rather, the MMP found in the supernatants were in the molecular weight range of gelatinases (such as MMP2 and MMP9) and membrane-type MMP (such as MMP14 and others), with differences between groups observed mainly in the weight range of the membrane-type MMP. This was interesting as recently, it was demonstrated that secreted MMP14 is a suitable predictor for MSC potency to reduce liver fibrosis [31]. Considering this, reduced MMP14 secretion and activation would represent a maladaptation of MSC in fibrotic environment, which may have to be addressed when attempting MSC-based therapies of ECM disease.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the MMP found in the supernatants were in the molecular weight range of gelatinases (such as MMP2 and MMP9) and membrane-type MMP (such as MMP14 and others), with differences between groups observed mainly in the weight range of the membrane-type MMP. This was interesting as recently, it was demonstrated that secreted MMP14 is a suitable predictor for MSC potency to reduce liver fibrosis [31]. Considering this, reduced MMP14 secretion and activation would represent a maladaptation of MSC in fibrotic environment, which may have to be addressed when attempting MSC-based therapies of ECM disease.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered MSC possesses an enhanced regulatory effect in inhibiting and reversing liver fibrosis. IC-2 engineered BM-MSC was proven to have the potential to relieve liver fibrosis (190). Just as indicated earlier, MSCs functionally alleviate liver fibrosis by producing cytokines or factors, directly acting on target cells, and secreting EVs.…”
Section: Liver Fibrosismentioning
confidence: 85%